Tangential Scleral Myopexy (TSM) as an Alternative to Muscle Resection in Strabismus Treatment - N. N. Pivovarov; E. N. Surkova (Oftalʹmologiâ)
To present the new method as a variant of minimal invasive strabismus surgery (MISS) technique for less invasive and faster reсtus muscle plication. Extraocular muscle strengthening is common for strabismus treatment. Plication as an alternative for tightening or strengthening muscles appears to be less traumatic, quicker and vascular preserving operation. A new plication variant performed by fixating the edge of muscle with 6-0 vicril sutures and pulling them forward and oversewn at 2–3 mm from external part sclera-tendon joint avoiding the anterior ciliary artereies. The distance of muscles advancement depends on the eye deviation angle and calculated by Kenneth Wright charts. In all patients fornix transconjunctival access was performed. Proposed trapezoidal scleral myopexy (TSM) was performed in 26 patients at the age from 3 to 32 years old (children 3–15 y.o. = 29; adults 20–32 y.o. = 7). 23 consecutive patients underwent TSM combined with antagonist recession at the same eye (15 esotropia, 11 exotropia). Follow up period was 6–26 months. The results were considered satisfactory if the postoperative angle was between 0 ± 3° (92.3 %). Only 2 cases (7.6 %) failed to reach this standart. The obtained results considered as very satisfactory. Patients reported only minimal postoperative discomfort and no complain on cosmetics. Trapezoidal muscle plication was inconspicuous throught the conjunctive. The good results of TSM proposed by the author seems to be very simple and more effective for muscle strengthening comparing to resection of medial and lateral rectus muscles. Placement of sutures at the muscle edge during trapezoidal plication exclude ciliary vassel destruction and anterior segment ischemia. The obtained results demonstrated that TSM was considered to be equivalent to resection of horizontal rectus and especially of vertical rectus muscles. Trapezoid form of plication increases the arc of sclera contact to the muscle, probably, explaining the efficiency of proposed operation for muscle strengthening. Proposed modification of muscle plication is reversible, simple, sparing for ciliary artery procedure and is recommended as minimal invasive strabismus surgery (MISS) for simultaneous operation on multiple rectus muscles.